Globalization and gender issue - Vineet Kaul, (Universiti Kebangsaan Malaysian, 2012)
Globalization has become the defining condition of the world in the twenty-first century. Yet, the impact of this changing world on women needs to be questioned because of continued inequalities and divisions. This article assesses various issues related to both women in the media and women and media, both as social issues in general and gender issues in particular. It is argued that globalization and the advancement in new media technologies are transforming how sexuality is viewed and treated around the world. The result is the beaming of homogeneous images in the media and the tendency towards increased cultural and social uniformity. This is exemplified by the way films, television and glitzy advertisements which have helped the spread of sales of products. The result can be seen in discriminatory advertising, and the spread of imposed images of femininity and female roles. The objective of this article is therefore to renew the reflection and interrogation on the media, using the gender paradigm.